The music lovers - Bowen, Catherine Drinker 1897-1973 (British Film Institute, 2024)
"Guided throughout by the swells and dips of Tchaikovsky's music, Ken Russell's film unfolds in opulent and fantastical musical sequences that portray scenes from the composer's life between 1875 and 1881. Touching on his disastrous marriage with Antonia Miliukova, his relationship with patroness Nadezhda von Meck and his repressed homosexuality, The Music Lovers is anchored by magnetic central performances from Glenda Jackson as Antonina, following her award-winning role in Women in Love, and Richard Chamberlain as a memorably neurotic Tchaikovsky."
Special features: Presented in High Definition ; Newly recorded audio commentary by film historian Matthew Melia ; "It runs in the family"(2024, 20 mins): Ken Russell's son Alexander Verney-Elliott looks back upon his father's work, and remembers his own appearance in The Music Lovers ; "Charlotte Brontë enters the Big Brother House" (2007, 16 mins): Ken Russell staged, directed and filmed this 'Radical Brontë' ballet for young people, illustrating Jane Eyre ; The Guardian Interview: Melvyn Bragg (1988, 76mins): ten years after the inception of "The Southbank Show", Melvyn Bragg discusses his career in television and film writer Ronald Harwood, at the National Film Theatre in London ; "Galina Ulanova in 'Swan Lake'" (1940, 6 mins): one of the greatest ballerinas of all time performs a dance from Tchaikovsky's masterpiece ; "Musical Highlights from USSR Today" (1953-56, 10 mins): edited highlights from three editions of the Soviet newsreel, gathering items about Tchaikovsky and Russian musical arts ; Costume designs: original sketches by Shirley Russell ; Original trailer
Verlagsnummer: BFIB1518
Original UK, 1971
Original aspect ratio 2.35:1
Keywords: Čajkovskij, Pëtr Ilʹič -- 1840-1893; Tchaikovsky, Peter Ilich / 1840-1893 / Drama; Composers / Drama; Man-woman relationships / Drama; Composers; Man-woman relationships; Biographical films; Drama; Feature films; Musical films; Film; Blu-Ray-Disc